(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Innovation activity in the context of globalization depends in its essence from external and internal factors of existence and is component in a system of general interconnection. Product of any national innovation system are intellectual property and patents are the main products that should be the standard effectiveness of the innovation system. In this regard, the state- promotes the development of science, innovation and invention and the improvement the role of intellectual property in our innovation activities countries.